Thrombin increases inflammatory cytokine and angiogenic growth factor secretion in human adipose cells in vitro - Phillips Shane A; Strande Jennifer L (BMC, 2009)
Abstract Background Abdominal obesity is associated with pro-thrombotic and inflammatory states. Therefore, the purpose of this study was to examine the expression of thrombin receptors (PAR1 and PAR4) human adipose tissue and whether thrombin stimulates an inflammatory cytokine and growth factor profile in human adipose tissue. Methods Human adipose tissue, isolated preadipocytes and differentiated adipocytes were used in this study. PAR1 and PAR4 mRNA and protein were detected by RT-PCR and immunoblot analysis in both adipose tissue and adipose microvessels. In separate studies, IL-1β, IL-6, MCP-1, TNF-α, IL-10, FGF-2, VEGF, and PDGF production were measured from adipose tissue (n = 5), adipocytes (n = 5), and preadipocytes (n = 3) supernatants with and without thrombin (1 or 10 U/ml; 24 hrs) treatment. Results Thrombin increased cytokine secretion of IL-1β, IL-6, MCP-1 and TNF-α and growth factor secretion of VEGF from adipocytes along with MCP-1 and VEGF from preadipocytes. The direct thrombin inhibitor lepirudin given in conjunction with thrombin prevented the thrombin-mediated increase in cytokine and growth factor secretion. Conclusion Here we show that thrombin PAR1 and PAR4 receptors are present and that thrombin stimulates inflammatory cytokine generation and growth factor release in human adipose tissue and cells in vitro. These data suggest that thrombin may represent a molecular link between obesity and associated inflammation.